Evolution in the real-world therapeutic strategies in more than 20, 000 women with breast cancer having received human epidermal growth factor receptor 2–targeted treatments: Results from the french personalized reimbursement model database (2011–2018). (December 2020) - Cottu, Paul; Coudert, Bruno; Perol, David; Doly, Anne; Manson, Julien; Aujoulat, Olivier; Barletta, Hugues; Chalabi, Nassera; Samelson, Laurence; Pivot, Xavier
Abstract: Background: There is a growing need for real-world data on cancer treatments usage, especially to assess compliance with recommendations. We developed a French project using hospital data to analyse evolution in the therapeutic strategies implemented in patients with human epidermal growth factor receptor 2 (HER2)–overexpressed (HER2+) breast cancer (BC) and exposed to injectable HER2-targeted therapies, i.e. trastuzumab, pertuzumab or trastuzumab emtansine (T-DM1). Patients and methods: Data from 26, 350 women with BC were extracted in September 2018 from the Electronic Pharmacy Record systems of 120 French randomly recruited hospitals. Evolution in the treatments used, and combination regimens were described from 2011, in accordance with the BC stage and treatment line. Results: Overall, 21, 119 patients treated since 2011 were analysed: 16, 398 patients with early BC (eBC) and 6030 patients with metastatic BC (mBC) including patients treated at both stages. In eBC, 89.2% of patients received trastuzumab combined with at least taxanes (trastuzumab–taxane–anthracycline: 62.6%). Patients with mBC were treated in the first line (80.3%) and/or the second line (40.1%) and/or ≥ the third line (28.3%). After its approval in 2014, pertuzumab was first used in first-line therapy combinations in 67.4% of the total cases, while trastuzumab–taxane decreased from 47.2% to 9.2%. Similarly, T-DM1 was used as the second-line treatment in 53.8% of cases. Conclusions: Given recent changes in available treatments for patients with HER2+ BC, this large French project provides robust information on real-world evolution in therapeutic strategies. Our data suggest there is room for significant improvement in optimal drug utilisation. Such data will be useful to build drug-related indicators for future value-based pricing solutions. Highlights: There is a growing need for real-world data on how cancer treatments are used. Use of therapies for early or advanced human epidermal growth factor receptor 2–positive (HER2+) breast cancer has changed over time. We provide real-world data on 2011–2018 evolution in injectable HER2 treatments. Results suggest that improvement is necessary for an optimal use. Drug-related indicators will be further built for value-based pricingsolutions.